Mapping Local Failure Following Bladder Radiotherapy According to Dose. Issue 10 (October 2022) - Abdel-Aty, H.; Warren-Oseni, K.; Bagherzadeh-Akbari, S.; Hansen, V.N.; Jones, K.; Harris, V.; Tan, M.P.; Mcquaid, D.; McNair, H.A.; Huddart, R.; Dunlop, A.; Hafeez, S.
Abstract: Aims: To determine the relationship between local relapse following radical radiotherapy for muscle-invasive bladder cancer (MIBC) and radiation dose. Materials and methods: Patients with T2-4N0-3M0 MIBC were recruited to a phase II study assessing the feasibility of intensity-modulated radiotherapy to the bladder and pelvic lymph nodes. Patients were planned to receive 64 Gy/32 fractions to the bladder tumour, 60 Gy/32 fractions to the involved pelvic nodes and 52 Gy/32 fractions to the uninvolved bladder and pelvic nodes. Pre-treatment set-up was informed by cone-beam CT. For patients who experienced local relapse, cystoscopy and imaging (CT/MRI) was used to reconstruct the relapse gross tumour volume (GTVrelapse ) on the original planning CT . GTVrelapse D98% and D95% was determined by co-registering the relapse image to the planning CT utilising deformable image registration (DIR) and rigid image registration (RIR). Failure was classified into five types based on spatial and dosimetric criteria as follows: A (central high-dose failure), B (peripheral high-dose failure), C (central elective dose failure), D (peripheral elective dose failure) and E (extraneous dose failure). Results: Between June 2009 and November 2012, 38 patients were recruited. Following treatment, 18/38 (47%) patients experienced local relapse within the bladder. The median time to local relapse was 9.0 months (95% confidence interval 6.3–11.7). Seventeen of 18 patients were evaluable based on the availability of cross-sectional relapse imaging. A significant difference between DIR and RIR methods was seen. With the DIR approach, the median GTVrelapse D98% and D95% was 97% and 98% of prescribed dose, respectively. Eleven of 17 (65%) patients experienced type A failure and 6/17 (35%) patients type B failure. No patients had type C, D or E failure. MIBC failure occurred in 10/17 (59%) relapsed patients; of those, 7/11 (64%) had type A failure and 3/6 (50%) had type B failure. Non-MIBC failure occurred in 7/17 (41%) patients; 4/11 (36%) with type A failure and 3/6 (50%) with type B failure. Conclusion: Relapse following radiotherapy occurred within close proximity to the original bladder tumour volume and within the planned high-dose region, suggesting possible biological causes for failure. We advise caution when considering margin reduction for future reduced high-dose radiation volume or partial bladder radiotherapy protocols. Highlights: Relapse following radical bladder radiotherapy most often occurs within the bladder. Local relapse occurs near the original MIBC tumour site and within the planned high dose region. In this high risk MIBC patient population, muscle invasive relapse was more common than non-muscle invasive relapse. Tumour dose escalation may be an appropriate future consideration; trial outcome data is awaited. Margin reduction should be considered with caution for reduced high-dose volume or partial bladder radiotherapy.